Experimental behaviour of stainless steel plate girders under combined bending and shear. (March 2020) - Chen, X.W.; Yuan, H.X.; Real, E.; Du, X.X.; Schafer, B.W.
Abstract: The behaviour of stainless steel plate girders subjected to combined bending and shear was experimentally studied in this paper. Both tensile and compressive material properties of the two adopted stainless steel alloys, including austenitic grade EN 1.4301 and duplex grade EN 1.4462, were determined by standard coupon tests. The three-dimensional (3D) optical scanning technology was introduced to acquire an accurate distribution of initial geometric imperfections for each plate girder specimen. A total of six plate girders were fabricated by hot-rolled stainless steel plates, and were tested to failure under combined bending and shear. In-depth analyses of the critical buckling characteristics, the ultimate resistances and the collapse behaviour of the tested specimens were all presented. The obtained ultimate resistances were further employed to assess the existing moment and shear (M-V) interaction design methods in EN 1993-1-5, GB 50017-2017, ANSI/AISC 360-16 and SEI/ASCE 8-02, and the design proposal presented by Jáger et al. It has been found that most of the existing codified M-V interaction formulae can be applicable for both carbon steel and stainless steel plate girders, yet they lead to relatively conservative predictions for stainless steel plate girders, except that the design method in ANSI/AISC 360-16 provides apparently unsafe strength predictions. Highlights: Six stainless steel plate girders are tested under combined bending moment and shear force. Initial geometric imperfections are accurately determined by three-dimensional optical scanning. Critical web buckling strengths are experimentally acquired based on measured surface strains. Shear stresses plus bending-induced compressive stresses lead to premature local web buckling. Most existing codified M-V interaction design curves provide safe but conservative predictions.